Influence of Scientific and Technical Progress on Change Management in Business and Education (Журнал "У". Экономика. Управление. Финансы., 2017)
The problem of scientific and technical progress influence on spheres of business and education, and also on their interaction is revealed in the article. Dynamics of development of management as a field of knowledge and professional activity is described. Technological tendencies, their influence on labor market and functioning of the organizations in the present and the future are analyzed.